ابن رشد في سياق استحضار قيم النهوض الحضاري الإسلامي المعاصر: دراسة نقدية تحليلية (Ibn Rushd in the Context of the Modern Muslim Civilizational Awakening: A Critical & Analytical Study) - Bekhouche, Abdelkader (Journal of Al-Tamaddun, 2020)
This research seeks to show the system of inter-cultural dialogue in Ibn Rushd’s thought and its impact on the real world around it. In this way, it is an attempt to search into Ibn Rushd’s writings in order to see if it is possible to deduce the cultural values of Ibn Rushd’s time from his philosophy. In order to reach this goal, the research addresses the following fundamental question: How do the cultural and intellectual values of co-existence appear in the thought of Ibn Rushd, and how are they expressed in his discourse and, moreover, why have they occupied a great significance in the universal cultural thought? This study establishes a great need for more such attempts demonstrating why Europe has admitted the impact of Ibn Rushd’s thought for a long time, particularly in terms of its role in activating the issues of the common and mutual cultural grounds in various fields. The methodology here depends largely on reading the opinions of Ibn Rushd in the area of inter-cultural dialogue between Greek, Jewish and Christian cultures. The readings of texts are classified in accordance with the goal of the study and then are analyzed and criticized objectively. The main result of this research is the fact that the mutual cultural common grounds and the feeling that human beings are part and parcel of the collective ego is very possible through the Islamic framework given in Ibn Rushd’s thought.